2013
DOI: 10.3109/10253890.2013.777832
|View full text |Cite
|
Sign up to set email alerts
|

Role of sex steroids in progesterone and corticosterone response to acute restraint stress in rats: sex differences

Abstract: Adrenal progesterone secretion increases along with corticosterone in response to stress in male and female rats to modulate some stress responses. Here we investigated the role of sex steroids in sex differences in the progesterone response to 60 min of restraint stress in adult male and female rats. Comparisons between males and females in the progesterone response were evaluated in parallel with corticosterone responses. From day 5 to 7 after gonadectomy, female and male rats were treated with estradiol or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
7
46
0
7
Order By: Relevance
“…In rats (males and females), we found that exposure to restraint stress evoked a parallel increase in secretion of both progesterone and corticosterone from the adrenal cortex (Kalil et al, 2013). Very recently, a parallel stress-induced increase in secretion of cortisol and progesterone has also been reported in humans (men and women) (Juster et al, 2016).…”
Section: Discussionsupporting
confidence: 49%
“…In rats (males and females), we found that exposure to restraint stress evoked a parallel increase in secretion of both progesterone and corticosterone from the adrenal cortex (Kalil et al, 2013). Very recently, a parallel stress-induced increase in secretion of cortisol and progesterone has also been reported in humans (men and women) (Juster et al, 2016).…”
Section: Discussionsupporting
confidence: 49%
“…We do not know tbe underlying regulations for tbis collapse of progesterone concentration. Basal plasmatic progesterone and cortisol concentrations were negatively correlated bowever, indicating a possible source of regulation between tbese two steroids (Cballis et al, 1971) as demonstrated in rats (Kalil et al, 2013). Glucocorticoids can affect gonadotropin-releasing bormone (GnRH) and luteinizing bormone (LH) secretions in rodents (Abima & Harlan, 1992;Kononen et al, 1992;Cbandran et al, 1994;Tilbrook et al, 2000).…”
Section: Discussionmentioning
confidence: 89%
“…[66,67]]. A significant contribution of the adrenal gland to Pg production as a stress response in OVX animals has been reported repeatedly [68,69,70]. Ovariectomy also resulted in up-regulation of IL-1 expression in the PVN regardless of stress exposure, suggesting that gonadal steroids exert an immunosuppressive effect on stress-induced cytokine expression.…”
Section: Discussionmentioning
confidence: 90%